2006
DOI: 10.1111/j.1365-2966.2005.09834.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tully-Fisher relation of intermediate redshift field and cluster galaxies from Subaru spectroscopy

Abstract: We have carried out spectroscopic observations in four cluster fields using Subaru's FOCAS multislit spectrograph and obtained spectra for 103 bright disc field and cluster galaxies at 0.06 z 1.20. 77 of these show emission lines, and 33 provide reasonably secure determinations of the galaxies' rotation velocity. The rotation velocities, luminosities, colours and emission-line properties of these galaxies are used to study the possible effects of the cluster environment on the star formation history of the gal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 67 publications
4
63
1
Order By: Relevance
“…For example Vogt et al (1996) reported very little evolution of the B-band TFR up to z ∼ 1, but other groups (e.g. Barden et al 2003;and Nakamura et al 2006) found a strong brightening of ∼1-2 mag in B-band luminosity over the same redshift range.…”
Section: The Tully-fisher Relation At Z ∼mentioning
confidence: 99%
“…For example Vogt et al (1996) reported very little evolution of the B-band TFR up to z ∼ 1, but other groups (e.g. Barden et al 2003;and Nakamura et al 2006) found a strong brightening of ∼1-2 mag in B-band luminosity over the same redshift range.…”
Section: The Tully-fisher Relation At Z ∼mentioning
confidence: 99%
“…Conselice et al 2005;Flores et al 2006;Atkinson et al 2007;Kassin et al 2007;Puech et al 2008;Cresci et al 2009;Gnerucci et al 2011) has been the subject of numerous works. Although many authors suggest the existence of evolution, observational results have not converged yet, and it is also unclear if the evolution is present in the zero point, the slope, or in both (Vogt et al 1996(Vogt et al , 1997Nakamura et al 2006). Recent observational results by Miller et al (2011) show evidence for a modest evolution of the sTFR by 0.04 ± 0.07 from z ∼ 1 to z ∼ 0.3 in the sense that at a given rotation velocity, galaxies have lower stellar masses in the past.…”
Section: Introductionmentioning
confidence: 99%
“…We followed other authors (e.g. Bamford et al 2006;Nakamura et al 2006;Vogt 2007) by adopting log(2V max ) as the dependent variable in the fit:…”
Section: Local Tully-fisher Relationmentioning
confidence: 99%
“…For instance, Nakamura et al (2006) study galaxies with i > 45 • , and Kassin et al (2007) choose spirals with 30 • < i < 70 • . In the first case, this restriction can include galaxies with large inclination errors (almost edge-on galaxies), and in both cases, the limits seem too restrictive.…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation